Computational modeling of bone allograft reconstruction following femoral shaft tumor resection: Investigating the impact of supplementary plate fixation. - Petr Boháč; Vasileios Apostolopoulos; Petr Marcián; Tomáš Tomáš; Michal Mahdal; Tomáš Návrat (PLoS ONE)
Background and objective The use of bone allograft reconstructions after tumor resection can introduce significant complications. Stable fixation is required to decrease the incidence of mechanical complications of segmental bone allografts. The purpose of the present study is to compare plating fixation methods of diaphyseal allografts after intercalary resection of the femur. Methods We created four defined fixation models using plates and/or intramedullary polymethylmethacrylate (PMMA) to simulate typical bone tumor resection with intercalary allograft reconstruction. One angularly stable plate (DFP) with 13 locking screws and fresh frozen allografts (labeled "I") were used for bone reconstruction. Three modified reconstructions were created: "II" included a supplementary plate (SP) with four locking screws, "III" was augmented with intramedullary PMMA in the allograft, and "IV" combined intramedullary PMMA and both plates. We applied a load model that simulates partial weight bearing on the lower limb to simulate the load during postoperative rehabilitation. Results The highest stress in the DFP occurred at the allograft-bone transition, with variant IV reaching 297 MPa. PMMA augmentation reduced median interfragmentary motion (IFM) and sliding distances, with variant III achieving the lowest distal sliding distance (0.9 μm) in the distal area. Supplementary plate fixation reduced maximal and median proximal IFM distances (86.9 μm in variant II vs. 116.0 μm in variant I) but increased sliding distances (23.7 μm in variant II vs. 0.6 μm in variant I). Conclusions PMMA augmentation reduces IFM and sliding distances, enhancing rigidity, particularly in the distal area. Supplementary plate fixation decreases IFM distances in the proximal area but increases sliding distances in the same region. Variants III and IV demonstrate lower IFM and sliding distances in the distal area overall. Variant III shows very low sliding distances in both distal and proximal areas. Variant IV combines improved firmness with slightly higher stress levels.